Constant Light in Critical Postnatal Days Affects Circadian Rhythms in Locomotion and Gene Expression in the Suprachiasmatic Nucleus, Retina, and Pineal Gland Later in Life - Kubištová, Aneta; Spišská, Veronika; Petrželková, Lucie; Hrubcová, Leona; Moravcová, Simona; Maierová, Lenka; Bendová, Zdeňka (Biomedicines, 2020)
The circadian clock regulates bodily rhythms by time cues that result from the integration of genetically encoded endogenous rhythms with external cycles, most potently with the light/dark cycle. Chronic exposure to constant light in adulthood disrupts circadian system function and can induce behavioral and physiological arrhythmicity with potential clinical consequences. Since the developing nervous system is particularly vulnerable to experiences during the critical period, we hypothesized that early-life circadian disruption would negatively impact the development of the circadian clock and its adult function. Newborn rats were subjected to a constant light of 16 lux from the day of birth through until postnatal day 20, and then they were housed in conditions of L12 h (16 lux): D12 h (darkness). The circadian period was measured by locomotor activity rhythm at postnatal day 60, and the rhythmic expressions of clock genes and tissue-specific genes were detected in the suprachiasmatic nuclei, retinas, and pineal glands at postnatal days 30 and 90. Our data show that early postnatal exposure to constant light leads to a prolonged endogenous period of locomotor activity rhythm and affects the rhythmic gene expression in all studied brain structures later in life.